Numerical analysis of soil deformation in the excavation with loose sand retained by inclined retaining piles - Wang, Yuping; Cheng, Xuesong; Zheng, Gang (Scientific reports, 2024)
Taking the conducted model test by authors as the research object, this paper first carries out detailed numerical analysis and verifies the reliability of the established model. Furthermore, the test phenomenon is explained based on numerical analysis, while parameter analysis is carried out, which mainly includes soil deformation between piles and soil deformation inside and outside excavation. The research results show that when the inclination angle of the piles is small (such as 10°), all or most of the soil (the range of the pile top to 0.6 L ) between the piles is compressed in the horizontal direction, and the piles and the soil between the piles can be regarded as a whole. When the inclination angle of the piles is large (such as 20°), all or most of the soil (the range of the pile top to 0.6 L ) between piles is in a relaxed state in the horizontal direction, and the piles deform independently. The research results also show that the maximum displacement of the soil on the surface outside the excavation occurs around the retaining pile, and the displacement distribution patterns change with different types of retaining structures and inclination angle.